Transcriptomic Responses of Adult Versus Juvenile Atlantids to Ocean Acidification - Ramos-Silva, Paula; Odendaal, Mari-Lee; Wall-Palmer, Deborah; Mekkes, Lisette; Peijnenburg, Katja T. C. A. (Frontiers in Marine Science, 2022)
Shelled holoplanktonic gastropods are among the most vulnerable calcifiers to ocean acidification. They inhabit the pelagic environment and build thin and transparent shells of aragonite, a metastable form of calcium carbonate. While shelled pteropods have received considerable attention and are widely regarded as bioindicators of ocean acidification, atlantids have been much less studied. In the open ocean, atlantids are uniquely positioned to address the effects of ocean acidification at distinct trophic levels. From juvenile to adult, they undergo dramatic metamorphosis. As adults they are predatory, feeding primarily on shelled pteropods, copepods and other zooplankton, while as juveniles they feed on algae. Here we investigated the transcriptome and the impact of a three-day CO2 exposure on the gene expression of adults of the atlantid Atlanta ariejansseni and compared these to results previously obtained from juveniles. Individuals were sampled in the Southern Subtropical Convergence Zone (Atlantic Ocean) and exposed to ocean chemistry simulating past (~mid-1960s), present (ambient) and future (2050) conditions. In adults we found that the changes in seawater chemistry had significantly affected the expression of genes involved in biomineralization and the immune response, although there were no significant differences in shell growth between the three conditions. In contrast, juveniles experienced substantial changes in shell growth and a broader transcriptomic response. In adults, 1170 genes had the same direction of expression in the past and future treatments when compared to the ambient. Overall, this type of response was more common in adults (8.6% of all the genes) than in juveniles (3.9%), whereas a linear response with decreasing pH was more common in juveniles (7.7%) than in adults (4.5%). Taken together, these results suggest that juveniles are more sensitive to increased acidification than adults. However, experimental limitations including short incubation times, one carboy used for each treatment and two replicates for transcriptome analysis, require us to be cautious about these conclusions. We show that distinct transcriptome profiles characterize the two life stages, with less than 50% of shared transcripts. This study provides an initial framework to understand how ocean acidification may affect the molecular and calcification responses of adult and juvenile atlantids.